Melamin toxicity in pigs - Lee, C. H.; Ooi, Peck Toung; Sheikh Omar, Abdul Rahman; Lim, B. K. (Universiti Putra Malaysia Press, 2011)
Three farms in Penang, Malaysia, reported illness in grower-finisher pigs with discarded kidneys from abattoir. Affected animals were inappetant, anorexic, thin, dull, and depressed. The episode was closely related with the feed formulation changes, where soybean and fishmeal were replaced with yeast. No significant mycotoxin levels were detected in both the feed and yeasts. However, high levels of melamine were detected in yeast (30,064 ppm) and finished feed (750 to 1500 ppm), which exceeded the acceptance level set by WHO (<2.5 ppm). Nonetheless, prominent gross abnormalities were detected, except for the lesions in the kidneys during necropsy. The affected kidneys were enlarged and yellowish in colour, firm in consistency and the cortical surface was wrinkled and dimpled. Dilated cortical and medullary lesions with yellow gritty crystalline materials were also observed. A microscopic examination revealed the lesions of acute tubular nephrosis, interstitial nephritis with multiple cysts in the kidney cortex. After the removal of the yeast source in the feed, the illness and kidney lesions were in remission.